# How do you simplify # [6 / (X-1)] = [4 / (X+1)]#?

By signing up, you agree to our Terms of Service and Privacy Policy

To simplify the equation [6 / (X-1)] = [4 / (X+1)], you can cross-multiply to eliminate the fractions. This gives you 6(X+1) = 4(X-1). Expanding the equation, you get 6X + 6 = 4X - 4. Simplifying further, you have 2X = -10. Dividing both sides by 2, you find that X = -5. Therefore, the solution to the equation is X = -5.

By signing up, you agree to our Terms of Service and Privacy Policy

- How do you evaluate #(-3y^2 - 7y - 2) - (5y^2 + 4y -5)#?
- James and Kathryn together had $190 in a savings bank. The amount in James's account was $30 more than 3 times the amount in Katherine's account. How much had each?
- Assume y varies inversely as x, if y=8 when x=4, how do you find x when y=2?
- If y varies directly as x, and y=42 as x=6, how do you find y for the x-value 3?
- How do you simplify #\frac { 9x + 81} { 4x ^ { 3} } \cdot \frac { x } { x ^ { 2} - 81}#?

- 98% accuracy study help
- Covers math, physics, chemistry, biology, and more
- Step-by-step, in-depth guides
- Readily available 24/7